The role of oxygen in the degradation of methylammonium lead trihalide perovskite photoactive layers - Aristidou,N; Sanchez-Molina,I; Chotchuangchutchaval,T; Brown,M; Martinez,L; Rath,T; Haque,SA (Angewandte Chemie-International Edition, 2015)
In this paper we report on the influence of light and oxygen on the stability of CH3NH3PbI3 perovskite-based photoactive layers. When exposed to both light and dry air the mp-Al2O3/CH3NH3PbI3 photoactive layers rapidly decompose yielding methylamine, PbI2, and I2 as products. We show that this degradation is initiated by the reaction of superoxide (O2−) with the methylammonium moiety of the perovskite absorber. Fluorescent molecular probe studies indicate that the O2− species is generated by the reaction of photoexcited electrons in the perovskite and molecular oxygen. We show that the yield of O2− generation is significantly reduced when the mp-Al2O3 film is replaced with an mp-TiO2 electron extraction and transport layer. The present findings suggest that replacing the methylammonium component in CH3NH3PbI3 to a species without acid protons could improve tolerance to oxygen and enhance stability.